Effects of the Vivifrail-B multicomponent exercise program based on society ecosystems theory on physical function in community-dwelling frail older adults: A randomized controlled trial - Yue Li; Shasha Li; Xu Weng; Xinyu Yang; Jianyi Bao; Shufang Liao; Yingxue Xi; Xiaofang Song; Guojing Guo (Experimental Gerontology)
Objective: The study aimed to explore the short and long-term effects of the Vivifrail-B multicomponent exercise based on society ecosystems theory on physical function in community-dwelling frail older adults. Methods: 59 older adults were randomly assigned to the intervention (n = 30) and control (n = 29) groups. The exercise was performed thrice a week for 12 weeks, with one offline group training and two at home training. The Tilburg Frailty Indicator (TFI), the Short Physical Performance Battery (SPPB), Handgrip strength (HGS), the Physical Self-Maintenance Scale (PSMS), and the Instrumental Activities of Daily Living Scale (IADL) were assessed at baseline, 6 weeks, 12 weeks, 18 weeks, and 24 weeks. Exercise compliance assessments and satisfaction surveys were conducted at post intervention. Generalized estimating equations was used to compare outcome measures. Results: At T1 (6-week), SPPB (P = 0.040) and PSMS (P = 0.042) of subjects in the intervention group were statistically different from the control group. At T2 (12-week), T3 (18-week) and T4 (24-week), all variables were significantly improved compared to the control group (all, P < 0.05), except for IADL (PT2 = 0.181, PT3 = 0.192, PT4 = 0.163). The short and long-term effects of the intervention were significant compared to the baseline level. However, the differences in Psychology (P = 0.699) and Society (P = 0.644) before and after the intervention were not significant. Conclusion: Vivifrail-B multicomponent exercise based on society ecosystems theory improved physical function of community-dwelling frail older adults, and the older adults' exercise compliance and satisfaction were high.